2019
DOI: 10.1016/j.jcot.2019.03.025
|View full text |Cite
|
Sign up to set email alerts
|

Allogenic umbilical cord blood-derived mesenchymal stem cells implantation for the treatment of juvenile osteochondritis dissecans of the knee

Abstract: Background: Osteochondritis dissecans (OCD) is a pathologic condition accompanied by the gradual destruction of subchondral bone and defects in the overlying articular cartilage. This case series reports the results of allogenic human umbilical cord blood-derived mesenchymal stem cell (hUCB-MSC) implantation for the treatment of osteochondral defect in two cases of juvenile osteochondritis dissecans. Case presentation: Two patients with osteochondral defect of the knee recovered from the disease enough to begi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…20 More recently, the mixture of hUCB-MSCs with HA has been used to repair large cartilage defects of the knee under arthrotomy. [8][9][10][11][12][13]21 Arthroscopy allows better visualization due to magnification, provides easier access to the cartilage defect approaching from several different angles, and leads to earlier gain of the range of motion and less scar formation compared with arthrotomy. However, arthroscopic hUCB-MSCs implantation is not easy because the collapse of anterior soft tissue might make the working space smaller and remnant saline solution might dilute hUCB-MSCs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…20 More recently, the mixture of hUCB-MSCs with HA has been used to repair large cartilage defects of the knee under arthrotomy. [8][9][10][11][12][13]21 Arthroscopy allows better visualization due to magnification, provides easier access to the cartilage defect approaching from several different angles, and leads to earlier gain of the range of motion and less scar formation compared with arthrotomy. However, arthroscopic hUCB-MSCs implantation is not easy because the collapse of anterior soft tissue might make the working space smaller and remnant saline solution might dilute hUCB-MSCs.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, open arthrotomy using a 3-5-cm incision often has been used for hUCB-MSCs implantation. [8][9][10][11][12][13]21 To achieve successful dry arthroscopy and safe implantation, several techniques have been applied to Before dry arthroscopy, retraction needle positioning and far medial working portal creation should be completed in conventional arthroscopy with saline solution. The holes should be created as close as possible for better coverage of the cartilage defect, but drilling should be performed carefully to avoid connecting neighboring holes, which might cause subchondral fracture.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… Notes : Many recent studies have evaluated allogeneic UC‐MSCs, 94 , 95 , 96 , 97 , 98 , 99 , 100 although there are many variations in dose, mode of application, the use in conjunction with surgical intervention, and addition of adjunctive therapeutic agents such as hyaluronic acid and somatotropin. Other cell sources, AD‐MSCs, BM‐MSCs, and synovial derived MSCs, continue to deliver promising results.…”
Section: Efficacy Of Recent Clinical Trials Utilizing Culture Expanded Allogeneic and Autologous Mscsmentioning
confidence: 99%
“…Several studies have shown that MSCs are involved in the maintenance and regeneration of connective tissues, and are known to migrate to tissues as a result of injury or inflammation, where they participate in the repair of damage [7][8][9] . Indeed, a recent case series report provided an option for treating juvenile OCD using human umbilical cord blood-derived mesenchymal stem cells (hUCB-MSCs) 10 . Further, a study on rats with articular cartilage defects demonstrated that SMSCs were able to differentiate into cartilaginous cells depending on the microenvironment 11 .…”
Section: Introductionmentioning
confidence: 99%